Preparação e propriedades de zeólitas faujasita contendo cátions amônio - Almeida, Karina Arruda; Martins, Leandro [UNESP]; Cardoso, Dilson (Sociedade Brasileira de Química, 2010)
Sodium faujasite zeolites with Si/Al ratio of 1.4 and 2.5 were exchanged with methylammonium cations. The influence of framework aluminum and ion exchange degree in their basic properties were evaluated. These properties were assessed in the Knoevenagel catalytic condensation. The sodium ion exchange was restricted to the supercavity and the exchange degree depended on the cation volume and on the Si/Al ratio. The higher catalytic activity is achieved for the zeolite with the lower Si/Al ratio exchanged with the monomethylammonium cation. The best performance of this catalyst is attributed to the higher basicity in combination with elevated micropore volume.
Preparation and properties of faujasite zeolites containing ammonium cations
Keywords: faujasite zeólitas; basic catalyst; methylammonium cations